Expression Patterns of Extracellular Matrix Proteins during Posterior Commissure Development - Stanic, Karen; Saldivia, Natalia; Förstera, Benjamín; Torrejón, Marcela; Montecinos, Hernán; Caprile, Teresa (Frontiers in Neuroanatomy, 2016)
Extracellular matrix (ECM) molecules are pivotal for central nervous system development, facilitating cell migration, axonal growth, myelination, dendritic spine formation, and synaptic plasticity, among other processes. During axonal guidance, the ECM not only acts as a permissive or non-permissive substrate for navigating axons, but also modulates the effects of classical guidance cues, such as netrin or Eph/ephrin family members. Despite being highly important, little is known about the expression of ECM molecules during central nervous system development. Therefore, this study assessed the molecular expression patterns of tenascin, HNK-1, laminin, fibronectin, perlecan, decorin, and osteopontin along chick embryo prosomere 1 during posterior commissure development. The posterior commissure is the first transversal axonal tract of the embryonic vertebrate brain. Located in the dorso-caudal portion of prosomere 1, posterior commissure axons primarily arise from the neurons of basal pretectal nuclei that run dorsally to the roof plate midline, where some turn towards the ipsilateral side. Expressional analysis of ECM molecules in this area these revealed to be highly arranged, and molecule interactions with axon fascicles suggested involvement in processes other than structural support. In particular, tenascin and the HNK-1 epitope extended in ventro-dorsal columns and enclosed axons during navigation to the roof plate. Laminin and osteopontin were expressed in the midline, very close to axons that at this point must decide between extending to the contralateral side or turning to the ipsilateral side. Finally, fibronectin, decorin, and perlecan appeared unrelated to axonal pathfinding in this region and were instead restricted to the external limiting membrane. In summary, the present report provides evidence for an intricate expression of different extracellular molecules that may cooperate in guiding posterior commissure axons.